Induction Somatic Embryogenesis Used 2,4-Dichlorophenoxyacetic Acid (2,4-D) and Kinetin in Spindle Leaf Explant Sugarcane - Wardatus Sholeha; Bambang Sugiharto; Dwi Setyati; Parawita Dewanti (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2015)
Induction of somatic embryogenesis in sugarcane requires the composition Plant Growth Hormone (PGH) appropriate. Utilizing of PGH (2,4-D and kinetin) is expected to induce sugarcane somatic embryogenesis. The purpose of this study was to obtain the concentration of 2,4-D and kinetin that effective for the multiplication of sugarcane var. NXI 1-3 through somatic embryogenesis. This study consists of four stages: callus induction, callus proliferation, regeneration of shoots and encapsulation. The plant material used is a spindle leaf sugarcane var. NXI 1-3. Callus induction used 2,4-D with different concentration (2 ppm, 3 ppm and 4 ppm). Callus proliferation used 2,4-D with concentration 1 ppm and 2 ppm. Regeneration of shoots used kinetin 0,5 ppm. The results are showed that the optimal induction of embryogenic callus on medium MS + sucrose 30 g / L + CH 300 ppm + 300 ppm PVP + 2,4-D 4 ppm as indicated by the high percentage of explants forming embryogenic callus that is equal to 40% and the respective concentration 2 ppm and 3 ppm is 33,3% and 37,5%. In proliferation stage, the development callus optimal on medium MS + sucrose 30 g / L + CH 300pm + PVP 300 ppm + 2,4-D 2 ppm and formulations for regeneration shoot on medium MS + sucrose 30 g / L + kinetin 0.5 ppm. The result of encapsulation can be shaped 100 sythetic seed. Keywords: Somatic embryogenesis, spindle leaf, kinetin, 2,4-D